Looming-eyes buoys fail to reduce seabird bycatch in the Icelandic lumpfish fishery: depth-based fishing restrictions are an alternative - Yann Rouxel; Hólmfríður Arnardóttir; Steffen Oppel (Royal Society Open Science, 2023)
Bycatch in gillnets from lumpfish (Cyclopterus lumpus) fisheries is an important conservation issue in the north Atlantic, with up to 30 000 seabirds potentially killed each year. To date, no technical solutions exist to reduce the bycatch of seabirds in gillnet fisheries, but research on above-water bird deterrents as a form of bycatch mitigation has shown promising results. Here, we tested whether a floating device called ‘looming-eyes buoy’ (LEB) would consistently reduce the bycatch of seabirds in the Icelandic lumpfish fishery. We conducted 61 controlled trials with sets of normal gillnets and experimental nets equipped with LEBs. We compared both fish catch and bycatch between net types while accounting for exposure time, water depth and season, and found no effect of LEBs on both target lumpfish catch and bycatch. Our analysis indicated however a strong correlation between bycatch rates and fishing depths, suggesting that depth-based fishing restrictions could virtually eliminate the bycatch of seabirds in this fishery. We estimated that limiting fishing to waters more than 50 m deep could save between 5000 and 9300 seabirds every year, arrest the population decline of endangered black guillemots in Iceland, while having only a marginal effect on target fish catch.